Validitas E-Modul Biologi Berbasis PBL Isu Lingkungan Lokal Tuban untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Afiya, Dina; Indrati, Dika Agustia (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to develop a Problem-Based Learning (PBL)-based biology e-module with a local theme from Tuban Regency, focusing on environmental issues. The study used a Research and Development (R&D) model with ADDIE stages limited to analysis, design, and development. The data collection instrument was a validation sheet that assessed the feasibility of the material, systematics, language, and media design and presentation. The results showed that the PBL-based biology e-module with a local theme from Tuban met the criteria of highly valid, with an average score of 81.75% from biology learning media expert validators and 97.5% from science learning material expert validators (biology). Based on these results, the developed e-module is suitable as a supporting teaching material in biology lessons for seventh-grade junior high school students on environmental issues with a local theme.